Efficacy and Safety of Amphotericin B Colloidal Dispersion via Nebulized Inhalation Combined with Intravenous Therapy for Invasive Pulmonary Fungal Disease: A Single-Center, Retrospective Cohort Study - Li Z; Li F; Chen T; Yang R (Infection and Drug Resistance)
Zhanjiang Li,1 Feng Li,2 Tengfei Chen,1 Rui Yang1 1Department of Respiratory Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of China; 2Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of ChinaCorrespondence: Rui Yang, Department of Respiratory Medicine, The First Affiliated Hospital of Zhengzhou University, No. 1 East Jianshe Road, Erqi District, Zhengzhou, 450052, People’s Republic of China, Tel +86-18203693330, Email yrain2012@126.comPurpose: To investigate the efficacy and safety of amphotericin B colloidal dispersion (ABCD) in treating invasive pulmonary fungal disease (IPFD) through nebulized inhalation combined with intravenous therapy.Methods: Patients diagnosed with IPFD who received ABCD from October 2023 to March 2024 were retrospectively enrolled. The treatment protocol for patient was determined by clinicians according to the patient’s condition and clinical practice. According to the treatment protocol, patients were divided into two groups: the ABCD nebulized inhalation combined with intravenous injection (combined therapy group) and the ABCD intravenous injection (intravenous therapy group). Clinical characteristics, ABCD administration (dose and duration), treatment outcomes (favorable response rate), and adverse events (AEs) were compared between the two groups.Results: Thirty-two patients were included, with 16 in each group. No significant differences were observed in the clinical characteristics between the two groups. In the combined therapy group, the numbers of proven, probable, and possible cases were 4 (25.00%), 7 (43.75%), and 5 (31.25%), respectively. In the intravenous injection treatment group, 1 (6.25%), 11 (68.75%), and 4 (25.00%) patients were proven, probable, and possible, respectively. The total dose of ABCD was slightly lower in the combined therapy group than in the intravenous therapy group (1675 vs 1800, P=0.611), although the difference was not statistically significant. The duration of combined therapy group was significantly shorter than that of the intravenous therapy group (8 vs 12, P=0.032), indicating that combination therapy can decrease the risk of hospital-acquired infections. The favorable response rate of the combined therapy group was significantly higher than that of the intravenous therapy group (93.75% vs 62.50%, P=0.033). Elevated urea levels emerged as the most common AE in the combined therapy group (68.75%) and intravenous therapy group (50.00%), no statistically significant difference was observed in the incidence of AEs between the two groups. All 32 patients (100%) completed the prescribed treatment regimen, and no patients withdrew from the study due to AEs.Conclusion: The efficacy of ABCD nebulized inhalation combined with intravenous injection was superior to intravenous injection of ABCD alone in the treatment of IPFD, with comparable safety and shortened medication time.Keywords: amphotericin B colloidal dispersion, invasive pulmonary fungal disease, nebulized inhalation, intravenous therapy